2013
DOI: 10.3389/fpubh.2013.00037
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Training Improves Health Workers’ Nutrition Knowledge and Competence to Manage Child Undernutrition: A Systematic Review

Abstract: Background: Medical and nursing education lack adequate practical nutrition training to fit the clinical reality that health workers face in their practices. Such a deficit creates health workers with poor nutrition knowledge and child undernutrition management practices. In-service nutrition training can help to fill this gap. However, no systematic review has examined its collective effectiveness. We thus conducted this study to examine the effectiveness of in-service nutrition training on health workers’ nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 47 publications
8
48
0
2
Order By: Relevance
“…Systematic reviews of in-service nutrition training have found that it improves the nutrition counselling and child undernutrition management of health workers (66,67) . In-service nutrition training programmes existed in less than half of the countries in West Africa and continuing training efforts were mainly concentrated on staff at national and regional levels, leaving health staff at lower levels with inadequate capacities in nutrition.…”
Section: Workforce Preparationmentioning
confidence: 99%
“…Systematic reviews of in-service nutrition training have found that it improves the nutrition counselling and child undernutrition management of health workers (66,67) . In-service nutrition training programmes existed in less than half of the countries in West Africa and continuing training efforts were mainly concentrated on staff at national and regional levels, leaving health staff at lower levels with inadequate capacities in nutrition.…”
Section: Workforce Preparationmentioning
confidence: 99%
“…Four reviews were included in this category (Forsetlund 2009;Reeves 2013;Horsley 2011;Sunguya 2013). The first review assessed the effects of educational meetings and workshops on professional practice and healthcare outcomes (Forsetlund 2009).…”
Section: Educational Meetings and Workhopsmentioning
confidence: 99%
“…Effects on critical appraisal skills were uncertain. None of the studies evaluated process of care or patient-related outcomes The final review assessed the effect of nutrition training of health workers on caregivers' feeding practices for children aged six months to two years (Sunguya 2013). The review identified ten studies.…”
Section: Educational Meetings and Workhopsmentioning
confidence: 99%
“…Although publications are merely one product of research and may not accurately characterize researcher training processes, previous authors have argued that African higher-education institutions do not have the means to provide adequate training to sustain home-grown leaders for nutrition . (Sunguya et al 2013). The review found that community health workers and other frontline workers were more likely to take on the shorter trainings.…”
Section: Competency Gaps In Africa Regarding Nutrition Professionalsmentioning
confidence: 99%